PENINGKATAN LITERASI BISNIS DIGITAL DALAM PENGELOLAAN USAHA TANI PERKOTAAN - Amalia Amalia; Muhammad Hasan; Citra Ayni Kamaruddin; Nurdiana Nurdiana; Nur Arisah (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
This study was made on the basis of the aim of knowing how far the development of digital business literacy in farming management is carried out by the Orchid Women Farmer Group located in Bara-Baraya Village, Makassar City. This study was conducted with a qualitative approach with a descriptive method. Data collection techniques in this study used observation techniques and interview techniques. There were 2 informants in this study, namely the chairman and treasurer of the Orchid Women Farmer Group. The selection of informants was done by purposive sampling technique. The results of this study suggest that digital business literacy is not carried out directly by members of the Orchid Farmer Women's Group, but is assisted by socialization and training held by the government and from Grab. As for things related to digital business literacy that can be developed by the Orchid Farmer Women's Group (1) Conducting meetings and discussions related to digital business and implementing it by creating digital content related to marketing of farm products (2) Conducting socialization related to increasing digital-based farming that is assisted in official application (3) Improving facilities that support literacy activities in collaboration with technology procurement